Individualized Hemodynamic Management in Newborns - de Boode, Willem P. (Frontiers in Pediatrics, 2020)
In our aim to improve patient outcome we are transitioning from a “one-size-fits-all” protocolized approach toward an individualized hemodynamic management, that is tailored to the cardiovascular (patho-)physiology and the specific clinical characteristics of each individual patient. In this narrative review an overview is provided about an individualized approach toward various neonatal hemodynamic conditions.